Effects of Betulinic Acid and Ursolic Acid on IL-17-Induced CCL20 Release in Normal Human Epidermal Keratinocytes - Anna Arai; Takahiro Oyama; Toyoaki Nakajima; Michiru Usui; Ena Sato; Takanori Kamiya; Midori Oyama; Takashi Tanikawa; Tomoharu Takeuchi; Takehiko Abe; Tomomi Hatanaka (Life)
Psoriasis is a chronic inflammatory skin disease characterized by erythema, infiltration, and scaling, which is mainly caused by interleukin (IL)-17. The use of molecular targeted drugs in specific therapies offers high efficacy; however, high medical costs and a significant risk of side effects highlight the need for novel therapeutic agents. We previously observed that Morus alba extract (MAE) suppressed IL-17-induced CCL20 mRNA expression in normal human epidermal keratinocytes (NHEKs). In this study, we focused on the IL-17 signaling pathway and investigated the effects of pentacyclic triterpenoids, betulinic acid (BA), and ursolic acid (UA), which are present in MAE, on NHEK cells. Real-time reverse transcription polymerase chain reaction (RT-PCR) and enzyme-linked immunosorbent assay (ELISA) revealed that both BA and UA suppressed CCL20 expression, while only UA alone inhibited CCL20 release. ELISA using specific inhibitors demonstrated that both the p38 and extracellular-signal-regulated kinase 1/2 (ERK1/2) pathways were crucial for IL-17-induced CCL20 release in NHEK. UA effectively suppressed ERK1/2 nuclear localization and moderately affected p38 phosphorylation. These results indicated that UA is a potential seed compound for psoriasis treatment through its targeting of the IL-17 pathway.